Beyond War: Russia, Ukraine and the State of the Field - Marco Puleri; Alessandro Achilli (eSamizdat)
The dramatic developments devastating Ukraine since February 2022 represent a true watershed not only for social and political dynamics in both countries, but also for Russian and Ukrainian studies. In this article, the authors aim to contribute to a preliminary review of the most relevant issues touched upon by the academic debate emerging in the months following the start of the war of aggression waged by the Russian Federation in Ukraine.